2015
DOI: 10.1021/acs.biochem.5b00989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Heme–DNA Complexes Composed of Some Chemically Modified Hemes and Parallel G-Quadruplex DNAs

Abstract: Heme {Fe(II)- or Fe(III)-protoporphyrin IX complex [heme(Fe(2+)) or heme(Fe(3+)), respectively]} binds selectively to the 3'-terminal G-quartet of a parallel G-quadruplex DNA formed from a single repeat sequence of the human telomere, d(TTAGGG), through a π-π stacking interaction between the porphyrin moiety of the heme and the G-quartet. The binding affinities of some chemically modified hemes(Fe(3+)) for DNA and the structures of complexes between the modified hemes(Fe(2+)) and DNA, with carbon monoxide (CO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 49 publications
3
67
0
Order By: Relevance
“…Parallel quadruplexes have more accessible ends, and a number of studies have shown that heme preferentially binds to parallel rather than antiparallel quadruplexes (Cheng et al, 2009;Kong et al, 2010;Kosman and Juskowiak, 2011). In vitro studies have shown that heme, like other porphyrins, binds to external guanines in a quadruplex, stacking like a slightly mismatched dinner plate on the planar ring of a terminal G-quartet (e.g., Yamamoto et al, 2015). PhenDC3 is also an end-binding quadruplex ligand and may therefore be well suited for heme displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Parallel quadruplexes have more accessible ends, and a number of studies have shown that heme preferentially binds to parallel rather than antiparallel quadruplexes (Cheng et al, 2009;Kong et al, 2010;Kosman and Juskowiak, 2011). In vitro studies have shown that heme, like other porphyrins, binds to external guanines in a quadruplex, stacking like a slightly mismatched dinner plate on the planar ring of a terminal G-quartet (e.g., Yamamoto et al, 2015). PhenDC3 is also an end-binding quadruplex ligand and may therefore be well suited for heme displacement.…”
Section: Discussionmentioning
confidence: 99%
“…Upon addition of a sto ichiometric oxidant (hydrogen peroxide, H 2 O 2 ), the complex was found to accelerate 250fold the oxida tion of the chromogenic substrate ABTS 78 ]) and the K + dependency of its catalytic activ ity, the authors wisely mused about its quadruplex struc ture 79 , which offers a defined binding site to hemin that becomes catalytically competent once nestled within this site only. It is intriguing that, more than three decades after its discovery, the precise mechanism of quadruplex DNAzyme remains unclear [80][81][82] , despite hundreds of new applications reported each year (for relevant reviews, see reFs [83][84][85]. Inspired by Sintim's work, Spinelli and col leagues further exploited the intramolecular assembly of TASQ to provide versatile catalytic systems (TASQzyme) that could be applied with a variety of precatalysts, cofactors and substrates 86 .…”
Section: Organic Frameworkmentioning
confidence: 99%
“…Indeed, as an iron containing, redox active, hydrophobic molecule, heme may catalyze spurious redox reactions that promote oxidative damage in the nucleus (Hanna et al, 2017; Reddi and Hamza, 2016). Alternatively, heme may act as an anti-proliferation signal through its ability to act as a transcriptional regulator by binding G-quadruplexes in DNA (Shinomiya et al, 2018; Shumayrikh et al, 2015; Yamamoto et al, 2015) or controlling transcription via Hap1 and the HAP complex (Buschlen et al, 2003; Hon et al, 2005; Zhang et al, 1993; Zhang and Hach, 1999; Zhang et al, 1998). Taken together, our results indicate that the relatively fast rate of nuclear heme acquisition may serve an important role in mitochondrial-nuclear retrograde signaling.…”
Section: Discussionmentioning
confidence: 99%